Effect of Subsurface Heterogeneous Correlated Hydraulic Properties on the Stochasti Behavior of the Unsteady Well Drawdown in a Confined Aquifer - Abdeen, Mostafa Ahmed Moawad; Abdin, Alaa E. (Engineering Transactions, 2006)
Groundwater is considered to be one of the most important water resources especially in areas where surface water resource, is not sufficient. However, utilizing this important groundwater resource requires a complete understanding of the groundwater flow behavior within the subsurface formations. The assumption of considering the subsurface formation as homogeneous media has been proven to be un-realistic. Therefore, the subsurface formation has to be considered as a heterogeneous structure in investigating the groundwater flow behavior. In addition, full understanding of the impact of the subsurface heterogeneous formation on the groundwater flow behavior is very essential in safe utilization of this important water resource. The current study investigates the impact of two subsurface heterogeneous correlated hydraulic properties on the stochastic behavior of a two-dimensional unsteady well drawdown in a confined aquifer. In addition, the presented study compares the impact of two subsurface heterogeneous cases. The first case considers two subsurface correlated hydraulic properties (current study), while the second case considers the heterogeneous subsurface hydraulic conductivity only. The two hydraulic properties considered in the current study are the subsurface hydraulic conductivity and storativity. The Monte Carlo stochastic approach is used in this study to perform various numerical computations required to assess the investigated problem. The results obtained from this study showed how important it was to consider and understand the heterogeneous subsurface formation and its impact on the groundwater flow behavior, since the two-dimensional unsteady well draw-down was greatly affected by the degree of heterogeneity and the correlation structure of the subsurface hydraulic properties.